Investor rewards to environmental responsibility: Evidence from the COVID-19 crisis - Garel, Alexandre; Petit-Romec, Arthur (Journal of Corporate Finance, 2021)
The COVID-19 shock and its unprecedented financial consequences have brought about vast uncertainty concerning the future of climate actions. We study the cross-section of stock returns during the COVID-19 shock to explore investors' views and expectations about environmental issues. The results show that firms with responsible strategies on environmental issues experience better stock returns. This effect is mainly driven by initiatives addressing climate change (e.g., reduction of environmental emissions and energy use), is more pronounced for firms with greater ownership by investors with long-term orientation and is not observed prior to the COVID-19 crisis. Overall, the results indicate that the COVID-19 shock has not distracted investors' attention away from environmental issues but on the contrary led them to reward climate responsibility to a larger extent.